Change Management In Islamic Education Forum In The Globalization Era Change Management In Islamic Education Forum In The Globalization Era - Siti Annisa Putri; Nuri Aslami (Journal of Indonesian Management, 2023)
This paper discusses the Change Management of Islamic Institutions in the Age of Globalization. Currently, Islamic educational institutions face various challenges such as the current of globalization, advances in science and technology, and rapid changes in the flow of information. In the era of technological advances, this is unavoidable because technology goes hand in hand with scientific advances. Every innovation is created to provide positive benefits for human life. Technology also provides many conveniences and new ways of carrying out human activities. Humans have enjoyed many benefits from the technological innovations produced in the last decades. Finding new ideas about change management in Islamic institutions is certainly not easy, therefore support from all parties is needed. In keeping pace with the development of Islam, adequate educational facilities are needed to educate students. Therefore, research on Islamic change management institutions in the era of globalization is very interesting to be disclosed further.